2010
DOI: 10.1111/j.1365-2664.2010.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Canada lynx reintroduction programme in Colorado: patterns in mortality

Abstract: Summary 1.Reintroducing carnivores has become a widely used technique to restore the natural integrity of ecosystems. Accurate estimates of demographic parameters for reintroduced populations are essential to evaluate the success of the reintroduction programme, assess the need to release additional animals and to develop management recommendations. 2. In an effort to establish a viable population of Canada lynx Lynx canadensis in Colorado, USA, the Colorado Division of Wildlife released 218 wild-caught lynx f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 26 publications
2
73
0
Order By: Relevance
“…For large carnivore reintroductions, however, evaluations commonly focus on behavioral, movement, genetic, or demographic aspects following reintroduction (De Barba et al, 2010;Devineau et al, 2010;Gusset, 2009;Preatoni et al, 2005). The few evaluations of post-release habitat selection that exist are often purely qualitative or descriptive (Breitenmoser et al, 2001;Hayward and Somers, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…For large carnivore reintroductions, however, evaluations commonly focus on behavioral, movement, genetic, or demographic aspects following reintroduction (De Barba et al, 2010;Devineau et al, 2010;Gusset, 2009;Preatoni et al, 2005). The few evaluations of post-release habitat selection that exist are often purely qualitative or descriptive (Breitenmoser et al, 2001;Hayward and Somers, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…During lows in the Snowshoe hare population cycle, large numbers of lynx may move southward into northern Minnesota in what has been termed an "invasion" (Mech 1973;Gunderson 1978;henderson 1978). Dispersing lynx have been documented venturing hundreds of kilometres into treeless habitats and crossing frozen lakes (Mech 1973;Gunderson 1978;ward and krebs 1985;Devineau et al 2010). Cochrane (2013) reported that ice-bridge formation was so substantial between Isle Royale and the mainland in the 1870s that draft horses and dog teams regularly crossed the ice.…”
Section: Discussionmentioning
confidence: 99%
“…Multi‐state models estimate 3 parameters including survival ( S ), detection ( p ), and transition probabilities (Lebreton et al ). In our case, we modeled alive and dead states and estimated apparent mortality rates as the transition probability true(trueψˆtrue) from an alive to a dead state (Lebreton and Pradel , Devineau et al ). Specifically, we modeled transitions from alive in the high or low development study areas to death by predation, malnutrition, or unknown mortality (ψˆHK,ψˆHM,ψˆHU,ψˆLK,ψˆLM,ψˆLU;0.0ex0.0ex0.3emFig.2).…”
Section: Methodsmentioning
confidence: 99%